2021
DOI: 10.1097/mcc.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring muscle mass using ultrasound: a key role in critical care

Abstract: Purpose of reviewThe loss of muscle mass in critically ill patients contributes to morbidity and mortality, and results in impaired recovery of physical functioning. The number of publications on the topic is increasing. However, there is a lack of consistent methodology and the most optimal methodology remains unclear, hampering its broad use in clinical practice. Recent findingsThere is a large variety of studies recently published on the use of ultrasound for assessment of muscle mass. A selection of studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
0
10
1
2
Order By: Relevance
“…Moreover, this effect was independent of the type and severity of the disease and of the therapeutic measures taken in the intensive care unit in our cohort. While the number of patients is similar in both studies, the APACHE II Score 23.5 (95% CI, 21.9-25.2) was higher than in our analysis 17 [10][11][12][13][14][15][16][17][18][19][20]. Annetta et al observed a significant 45% decrease in rectus femoris cross-sectional area over a 20-day ICU stay in a cohort of 38 young trauma patients, meanwhile tibialis anterior CSA reduction of 22% was nonsignificant.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Moreover, this effect was independent of the type and severity of the disease and of the therapeutic measures taken in the intensive care unit in our cohort. While the number of patients is similar in both studies, the APACHE II Score 23.5 (95% CI, 21.9-25.2) was higher than in our analysis 17 [10][11][12][13][14][15][16][17][18][19][20]. Annetta et al observed a significant 45% decrease in rectus femoris cross-sectional area over a 20-day ICU stay in a cohort of 38 young trauma patients, meanwhile tibialis anterior CSA reduction of 22% was nonsignificant.…”
Section: Discussioncontrasting
confidence: 51%
“… 9 11 Assessment of the quadriceps muscle has been used extensively to assess muscle wasting with ultrasound in the critically ill. 12 The rectus femoris muscle is often used to evaluate muscle cross-sectional area as a surrogate for whole-body skeletal muscle. 13 , 14 Either the rectus femoris or quadriceps (sum of rectus femoris and vastus intermedius muscle thickness) is frequently measured for muscle thickness. Both CSA and thickness measurements have been shown to decline early during the course of critical illness and have been inconsistently associated with impairment of strength and physical function.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis suggests that a daily loss of about 2% can be estimated, whereby ultrasound is the most frequent used method to detect and monitor muscle degradation [ 66 ]. Hereby, surrogate parameters for the quantification of muscle mass are the muscle layer thickness (MLT) and the muscle CSA [ 67 ]. The MLT is usually determined in sonographic short axis as the maximum vertical diameter of muscle tissue within the muscle fascia.…”
Section: Current State Of Nmus In Icuawmentioning
confidence: 99%
“…Furthermore, there is a strong correlation between muscle strength and the CSA of the rectus femoris (RF) muscle. Studies conducted in ICU have shown that muscle mass can decrease rapidly, with a 10% decline in the RF' CSA within 7 days [ 80 ].…”
Section: Imagingmentioning
confidence: 99%